Perlindungan Hukum dalam Pengalihan Karya Musik yang Diunggah pada Sosial Media - I Made Dwi Darmestha; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2019)
Song or music works become an unique creation in one part of the copyright itself where song ormusic works are intangible but have legal power in copyright and do not need to be registered to recognize the work. And the transferof song or music works will be enjoyed as a whole, especially to its creator, the copyright holder, and the community. In its development, covering songs become a term in the transfer of song ormusic works. The need of law in protecting the transfer of song ormusic works, especially in the work uploaded on social media. The formulation of the problem in this study is 1. How is the legal certainty of the transfer of music to others? 2. How is the legal protection of copyright holders over the transfer of music that is uploaded through social media? This study uses normative legal research methods, uses a legal approach and conceptual approach, examines primary legal materials, secondary legal materials, and tertiary legal materials and uses legal material collection techniques with library studies, reading literature and related internet pages. The activity of transferring copyright in a musical work or referred to as covering a song where the legality can be carried out by someone else in someone's work in connection with the existence of a license and related royalties. This legal arrangement is basically still legal even though the law is in Law No. 28 of 2014 concerning License licensing rights and royalties in transfers. In the covered music and uploaded on social media, for example youtube, in the current development, YouTube has become an activity that produces economic value.In other words, when there is a copyright transfer, especially song atau music works from someone who is not the creator of the work and uploaded to the social media in general, a creator's license must be included.In connection with the economic value contained in social media, it means that the economic right of a work participates in switching.In other words, there is a royalty that must be given to the owner or creator of a song atau music works.